Disarranging Narrative: Review of Louise Green, Fragments from the History of Loss: The Nature Industry and the Postcolony - Nuttall, Sarah (Humanimalia, 2024)
Review of: Louise Green, Fragments from the History of Loss: The Nature Industry and the Postcolony. AnthropoScene: The SLSA Book Series. University Park: Pennsylvania State University Press, 2020. 7 b&w illus. x + 193 pp. 29.95 (pb).